2006
DOI: 10.1536/ihj.47.775
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Right Ventricular Dilatation and Troponin I Elevation in Acute Pulmonary Embolism

Abstract: SUMMARYAcute pulmonary embolism continues to cause significant morbidity and mortality despite advances in diagnosis and treatment. This retrospective analysis aimed to determine whether the combination of elevated troponin I and right ventricular dilatation (RVD) could provide a more powerful predictor for risk evaluation.The study data comprised records of 110 patients with either high-probability ventilation/perfusion lung scan or positive spiral computed tomography. All cause 100-day mortality was 18.2%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…19,20,27,28 The main features of the selected studies are reported in Table 1. Demographic features of study populations (age, gender) were similar across the studies, and almost all the included patients had an objective diagnosis of pulmonary embolism.…”
Section: Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20,27,28 The main features of the selected studies are reported in Table 1. Demographic features of study populations (age, gender) were similar across the studies, and almost all the included patients had an objective diagnosis of pulmonary embolism.…”
Section: Selected Studiesmentioning
confidence: 99%
“…In 2 studies, mortality was available only at 90 days 24,26 ; in a third study, mortality was available only at 100 days. 28 …”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Others described this combination among unstable as well as stable patients. 4,20,[22][23][24][25][26][27] We were unable to identify investigations of patients with PE in which levels of cTnI consistent with acute myocardial infarction in combination with RV size were described.…”
Section: Discussionmentioning
confidence: 99%